Detection of methicillin‐resistant Staphylococcus aureus persistence in osteoblasts using imaging flow cytometry. Issue 5 (1st April 2020) - Bongiorno, Dafne; Musso, Nicolò; Lazzaro, Lorenzo Mattia; Mongelli, Gino; Stefani, Stefania; Campanile, Floriana
Abstract: Methicillin‐resistant S. aureus has been reported as the main pathogen involved in chronic infections, osteomyelitis, and prosthetic joint infections. The host/pathogen interaction is dynamic and requires several changes to promote bacterial survival. Here, we focused on the internalization and persistence behavior of well‐characterized Staphylococcus aureus invasive strains belonging to the main ST‐MRSA‐SCC mec clones. To overcome the limitations of the cell culture method, we comparatively analyzed the ability of internalization within human MG‐63 osteoblasts with imaging flow cytometry (IFC). After evaluation by cell culture assay, the MRSA clones in the study were all able to readily internalize at 3h postinfection, the persistence of intracellular bacteria was evaluated at 24h both by routine cell culture and IFC assay, after vancomycin‐BODIPY staining. A statistical difference of persistence was found in ST5‐SCC mec II (26.59%), ST228‐SCC mec I (20.25%), ST8‐SCC mec IV (19.52%), ST239‐SCC mec III (47.82%), and ST22‐SCC mec IVh (50.55%) showing the same ability to internalize as ATCC12598 (51%), the invasive isolate used as control strain for invasion and persistence assays. We demonstrated that the intracellular persistence process depends on the total number of infected cells. Comparing our data obtained by IFC with those of the cell culture assay, we obtained greater reproducibility rates and a number of intracellular bacteria, with the advantage of analyzing live host cells. Moreover, with some limitations related to the lack of whole‐genome sequencing analysis, we validated the different proclivities to persist in the main Italian HA‐MRSA invasive isolates and our results highlighted the heterogeneity of the different clones to persist during cell infection. Abstract : MRSA has been reported as the main pathogen involved in osteomyelitis and prosthetic joint infections. The host/pathogen interaction is dynamic and requires several changes to promote bacterial survival. Here, we focused on the internalization and persistence behavior of Staphylococcus aureus invasive strains belonging to the major MRSA clones, within human MG‐63 osteoblasts. We used imaging flow cytometry, a technique able to analyze living host cells. We demonstrated that the intracellular persistence process is different among clones and depends on the total number of infected cells instead of the number of intracellular bacteria.